PENERAPAN SELF HEALING TERHADAP PENURUNAN SKALA NYERI PASIEN POST OPERASI DI RSUD UNGARAN - Ainnur Rahmanti; Sonia Ambar (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2021)
Almost all surgeries cause pain, the pain that is felt is the result of the incision. One intervention to relieve postoperative pain is Self healing. The purpose of this case study is to describe the reduction in pain scale of postoperative patients in Cempaka Room Ungaran Regional Hospital after self-healing intervention. This type of research is descriptive using a case study approach. The subjects in this study were 2 postoperative patients with criteria of mild to moderate pain. Analysis of pain measurements using the Numerical Scalel Branch scale. The analysis showed that there was a decrease in pain scale after the intervention. On subject 1 the pain scale 3 (mild pain) became the pain scale 1 (mild pain) and subject 2 the pain scale 4 (moderate pain) became the pain scale 1 (mild pain). Effective self healing therapy is used to reduce postoperative pain in the room because it is easy and simple. Good therapy is applied by nurses in the room to reduce the scale of pain in postoperative patients.